Understanding addiction - Henderson, Elizabeth Connell (Understanding health and sickness series., 2000)
A concise overview of this complex affliction for all those affected by addiction -- addicts, family members, and even employers. Download Plain Text version. At least one of every four people in America has had some experience with addiction -- either personally or through a family member. Addiction and its consequences cost billions of dollars each year in direct medical costs, lost productivity, accidents, crime, and corruption. Yet as a disease, addiction is still largely misunderstood. Starting with the question "what is addiction?" Elizabeth Connell Henderson takes the reader t